Nutrient fuxes from an Arctic seabird colony to the adjacent coastal marine ecosystem - Finne, Eirik Aasmo; Varpe, Øystein; Durant, Joël; Gabrielsen, Geir W.; Poste, Amanda (Polar Biology, 2022)
Seabirds are important vectors for nutrient transfer across ecosystem boundaries. In this seasonal study, we evaluate the impact of an Arctic colony (Alkhornet, Svalbard) of Black-legged Kittiwakes (Rissa tridactyla) and Brünnich’s Guillemots (Uria lomvia) on stream nutrient concentrations and fuxes, as well as utilization by coastal biota. Water samples from seabird-impacted and control streams were collected regularly throughout the melt season (June–September) for nutrient and organic carbon analysis. Stable carbon and nitrogen isotope analysis (δ 13 C and δ 15 N) was used to assess whether seabirdderived nitrogen (N) could be traced into flamentous stream algae and marine algae as well as consumers (amphipods). Concentrations of nitrate (NO 3 − ) and nitrite (NO 2 − ) peaked in July at 9200 µg N L −1 in seabird-impacted streams, 70 times higher than for control streams. Mean concentrations of phosphate (PO 4 3− ) in seabird-impacted streams were 21.9 µg P L −1 , tenfold higher than in controls. Areal fuxes from seabird-impacted study catchments of NO 3 − + NO 2 − and PO 4 3− had estimated ranges of 400–2100 kg N km −2 and 15–70 kg P km −2 , respectively. Higher δ 15 N was found in all biota collected from seabird-impacted sites, indicating utilization of seabird-derived nitrogen. Acrosiphonia sp. from seabird-impacted sites had higher δ 15 N values (20–23‰ vs. 3–6‰) and lower C:N ratios (10.9 vs. 14.3) than specimens collected from control sites, indicating reliance on seabird-derived nitrogen sources and potentially higher N-availability at seabird-impacted nearshore sites. Our study demonstrates how marine nutrients brought onshore by seabirds also can return to the ocean and be utilized by nearshore primary producers and consumers.